The Influence of Green Marketing and Environmental Knowledge on Buying Decision Through Buying Interest of LocknLock Customers - Widyasari, Maya; Handayani, Siti Dyah (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2021)
This research aims to analyze the effect of green marketing and environmental knowledge directly and indirectly on buying decisions through buying interest as a mediating variable. This research method used is quantitative approach and conducted on customers of LocknLock kitchen and household products with a total sample of 120 respondents obtained through a questionnaire method. The sampling technique used was purposive sampling method based on the criteria of customers who live in the Province of D.I. Yogyakarta and have purchased a product at least once. The analytical method used is the Structural Equation Modelling (SEM) method processed through the AMOS 22.0 application. The results show following facts: green marketing and environmental knowledge have significant and positive effect on buying intention; green marketing has no effect on buying decisions; environmental knowledge has a significant and positive effect on buying decisions; buying intention has a significant and positive effect on buying decisions; buying intention is proven to be a mediating variable on green marketing relationship with buying decisions; buying interest is not proven to be a mediating variable on the relationship between environmental knowledge and buying decisions. The study explained that the better and more active companies in doing green marketing and more educated customers about the importance of preserving the environment through the use of green products will increase the interest of buying customers that eventually lead to decision purchases.